Złoża kopalin w systemie planowania przestrzennego województwa lubuskiego = Minerals deposits in spatial planning system of Lubuskie Voivodeship - Kot-Niewiadomska, Alicja (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Activities related to the protection of mineral deposits in Lubuskie Voivodeship, should be evaluated positively both in the current and projected Voivodeship Spatial Development Plan. Furthermore, the arrangements from this document should be transported in to local (community) spatial planning documents. In this regard, many of the analyzed communes, should update their Study of Conditions and Directions of Spatial Management in the scope of possible mining activity. This is a significant issue because the legal instruments of unexploited mineral resources protection, in accordance with Polish law, at the moment are stated only in spatial planning documents.
Keywords: ochrona złóż kopalin; województwo lubuskie; planowanie przestrzenne; protection of minerals deposits; lubuskie voivodeship; spatial planning